Միհրան Թումաճանը՝ Բարսեղ Կանաչյանի «Նանորի» մասին - Սաթենիկ Ղափլանյան (ՀՀ ԳԱԱ հրատ.)
Статья посвящена Предисловию-указателю Миграна Тумачана к хоровому произведению a cappella “Нанор” Барсега Каначяна. Письмо Миграна Тумачана священнику латакийской епархии отцу Сурену Папахяну и упомянутое Предисловие-указатель вводятся в научный оборот впервые. Автор исследования приходит к выводу, что Предисловие-указатель Миграна Тумачана к “Нанор” – своеобразный исторический очерк с анализом и изложением собственной точки зрения на традиционные нацональные обряды. This article considers Mihran Tumachan’s Preface-guideline to “Nanor” –an a capella choral work by Barsegh Kanachyan. This Preface-guideline to “Nanor” together with Mihran Tumachyan’s letter, addressed to Father Suren Papakhyan, a cleric of Latakia diocese are introduced for the first time to academic circles. Ghaplanyan comes to the conclusion that Tumachan’s prologue-guide to "Nanor" is a kind of historical resume, as well as a review where the point of view of Tumachyan on national traditional rituals has been narated.
Keywords: M Music and Books on Music; Vocal Music